STATIC ANALYSIS OF THE SPINDLE SHAFT WITH A SPLIT CYLINDER - Mirzaumidov, Asilbek; Azizov, Javlonbek; Siddiqov, Anvarbek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article examines the static analysis of a split-cylinder shaft and the process of calculating its torsion angle along with its strength. Using static analysis, forces, moments, stresses, and deformations acting on the shaft are determined. The research focuses on calculating the strength of the split-cylinder shaft in initial cotton processing enterprises and ensuring that the torsion angle remains within the permissible limits. The static equilibrium process, the uniform distribution of forces, shear forces, and moment diagrams are analyzed in detail. Additionally, the article provides information about the material properties of the shaft and its performance under mechanical conditions. The study also highlights the importance of both static and dynamic equilibrium, as well as the necessary measures to improve safety and economic efficiency in technological machinery operations. This article offers practical recommendations for improving the construction of split-cylinder shafts and ensuring their effective performance in industrial sectors.